Pectobacterium carotovorum subsp. carotovorum – the causal agent of broccoli soft rot in Serbia - Gašić, Katarina; Gavrilović, Veljko; Dolovac, Nenad; Trkulja, Nenad; Živković, Svetlana; Ristić, Danijela; Obradović, Aleksa (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Soft rot symptoms were observed on broccoli plants in several commercial fields in thewestern part of Serbia. Six strains of bacteria were isolated from diseased tissues and identified as Pectobacterium carotovorum subsp. carotovorum using conventional bacteriological and molecular methods. All strains were non-fluorescent, gram-negative, facultative anaerobes, oxidase-negative and catalase-positive, causing soft rot on potato and carrot slices and did not induce hypersensitive reaction on tobacco leaves. They grew in 5% NaCl and at 37°C, did not produce acid from α-methyl glucoside, sorbitol and maltose, nor reducing substances from sucrose, but utilized lactose andtrehalose, and did not produce indole or lecithinase. The investigated strains showed characteristic growth on Logan’s medium and did not produce blue pigmented indigoidine on GYCA medium nor “fried egg” colonies on PDA. The identity of strains was confirmed by ITS-PCR and ITS-RFLP analyses and by sequence analysis of the 16S rRNA gene. In a pathogenicity assay, all strains caused tissue discoloration and soft rot development on inoculated broccoli head tissue fragments.
Keywords: Broccoli; Pectobacterium carotovorum subsp. carotovorum; soft rot; 16S rRNA gene; ITS-PCR-RFLP